Cost of Illness pada Pasien Hipertensi Rawat Jalan di Puskesmas Gamping 2 - Andriani, Yuni; Wulandari, Sephia; Larasati, Niken (UI Scholars Hub, 2025)
Hypertension is characterized by increased blood pressure due to various risks that do not function normally in stabilizing blood pressure. According to WHO, the number of hypertension patients worldwide in 2020 reached 972 million (26.4%) and increased in 2021 to 1.2 billion (29.2%). Hypertension treatment must be carried out long, requiring a substantial aggregate treatment cost. Based on BPJS data, in 2014, hypertension accounted for approximately Rp2.8 trillion in healthcare costs, which increased annually until 2016, reaching around Rp4.2 trillion. The purpose of this study is to describe the overall estimated cost of hypertension treatment for outpatients at Puskesmas Gamping 2. This Cost of Illness (COI) study calculates direct and indirect costs from the perspectives of payers and patients. The study was conducted on 65 respondents selected using the convenience sampling technique. The research instruments included the collection of financial administration information and medical records. The study results show that the majority of outpatient hypertension patients at Puskesmas Gamping 2 are female, totaling 41 patients (63%), aged 55-64 years (27 patients, 42%), and working as housewives (27 patients, 42%). The average total cost (COI) of outpatient hypertension treatment at Puskesmas Gamping 2 is Rp1,852,392, with a minimum cost of Rp772,886 and a maximum of Rp3,837,080 per patient per year. These results indicate the need for a more effective and efficient hypertension management strategy, both clinically and economically, to reduce the continuously increasing financial burden on the healthcare system and patients.